Behavior of the Alternative Types of USBR Basin with Changes in the Geometric Characteristics of the Straight Walls of the Stilling Basin - Hadi, Humam Amer; Al-Qaisi, Atheer Zaki (Engineering, Technology & Applied Science Research, 2025)
A stilling basin is a vital energy dissipator structure that transitions supercritical flow from a dam spillway into subcritical flow to protect downstream (ds) riverbeds from the scouring caused by high-velocity water. This study evaluates the impact of wall configurations and middle blocks on energy dissipation efficiency in stilling basins by modifying wall shapes and incorporating middle blocks. Five cases were tested: flat walls with middle blocks (Case 1), small zigzag walls without and with middle blocks (Cases 2 and 3), and large zigzag walls without and with middle blocks (Cases 4 and 5). A total of 55 experiments were conducted with discharges ranging from 0.010 m³/s to 0.020 m³/s. The average energy dissipation rates were 61.1%, 58.5%, 65.2%, 63.6%, and 64.9% for Cases 1, 2, 3, 4, and 5, respectively. Case 3, featuring small zigzag walls with middle blocks, demonstrated the highest energy dissipation efficiency, outperforming the other cases. This research highlights innovative designs for stilling basins, enhancing energy dissipation efficiency and mitigating the ds scouring effects.